Operational Research Applied to Management: a study of international articles published between 1993 - 2013 - Santos, Wellington Furtado; Simonetto, Eugenio de Oliveira; Ferreira, David Luiz Silva (Revista de Administração da UFSM, 2017)
This study examines the international scientific literature in operations research applied to management, published between the years 1993 - 2013. Regarding the results of the last years there has been an increase of 1500% in the number of articles published in this area. The largest share of published articles belongs to the European continent with 46.36% of the publications in the last 20 years. The supply chain with 9.6% is the topic that attracts interest in publishing articles. The relevance can be verified by its index h = 21, this period 176 articles were published in international operations research applied to management.